Longitudinal course of disaster-related PTSD among a prospective sample of adult Chilean natural disaster survivors. (8th June 2016) - Fernandez, Cristina A; Vicente, Benjamin; Marshall, Brandon DL; Koenen, Karestan C; Arheart, Kristopher L; Kohn, Robert; Saldivia, Sandra; Buka, Stephen L
Abstract: Background: With an increasing number of individuals surviving natural disasters, it is crucial to understand who is most at risk for developing post-traumatic stress disorder (PTSD). The objective of this study was to prospectively examine the role that pre-existing psychopathology plays in developing PTSD after a disaster. Methods: This study uses data from a prospective 5-wave longitudinal cohort (years 2003-11) of Chilean adults from 10 health centres ( N  = 1708). At baseline, participants completed the Composite International Diagnostic Interview (CIDI), a comprehensive psychiatric diagnostic instrument. In 2010, the sixth most powerful earthquake on record struck Chile. One year later, a modified version of the PTSD module of the CIDI was administered. Marginal structural logistic regressions with inverse probability censoring weights were constructed to identify pre-disaster psychiatric predictors of post-disaster PTSD. Results: The majority of participants were female (75.9%) and had a high-school/college education (66.9%). After controlling for pre-disaster PTSD, pre-existing dysthymia [odds ratio (OR) = 2.21; 95% confidence interval (CI) = 1.39-3.52], brief psychotic disorder (OR = 2.67; 95% CI = 1.21-5.90), anxiety disorders (not including PTSD; OR = 1.49; 95% CI = 1.27-1.76), panic disorder (OR = 2.46; 95% CI = 1.37-4.42), agoraphobia (OR = 2.23; 95% CI = 1.22-4.10), social phobia (OR = 1.86; 95% CI = 1.06-3.29), specific phobia (OR = 2.07; 95% CI = 1.50-2.86) and hypochondriasis (OR = 2.10; 95% CI = 1.05-4.18) were predictors of post-disaster PTSD. After controlling for pre-disaster anxiety disorders, dysthymia, and non-affective psychotic disorders, individuals with pre-disaster PTSD (vs those without pre-disaster PTSD) had higher odds of developing post-disaster PTSD (OR = 2.53; 95% CI = 1.37-4.65). Conclusions: This is the first Chilean study to demonstrate prospectively that pre-disaster psychiatric disorders, independent of a prior history of other psychiatric disorders, increase the vulnerability to develop PTSD following a major natural disaster.